Psychometric Properties of the Test of Existential Motivations in Young Adults - Mercado Maya, Aída (2019)
The purpose of this study was to obtain the psychometric properties of the Test of Existential Motivations created by Längle & Eckhard in a sample of young adults living in the metropolitan area of the Valle de Toluca, Mexico. The instrument was assessed in 300 subjects. Based on the statistical analysis, it can be concluded that the test is adequate to measure existential motivations in young adults, considering the evidence of reliability and validity.